REV-ERB and ROR nuclear receptors as drug targets - Kojetin, Douglas J. (Nat Rev Drug Discov, 2014)
The nuclear receptors REV-ERB (consisting of REV-ERBα and REV-ERBβ) and retinoic acid receptor-related orphan receptors (RORs; consisting of RORα, RORβ and RORγ) are involved in many physiological processes, including regulation of metabolism, development and immunity as well as the circadian rhythm. The recent characterization of endogenous ligands for these former orphan nuclear receptors has stimulated the development of synthetic ligands and opened up the possibility of targeting these receptors to treat several diseases, including diabetes, atherosclerosis, autoimmunity and cancer. This Review focuses on the latest developments in ROR and REV-ERB pharmacology indicating that these nuclear receptors are druggable targets and that ligands targeting these receptors may be useful in the treatment of several disorders.